The intercultural approach In the english lesson teaching Everyday Culture To Upper Primary Students - Kanfi-Horvát Erzsébet; Sinka Hilda (2006)
In my thesis I intend to prove that primary school students do not have enough knowledge about the everyday culture of the English people and they do not have enough opportunities in the English lessons to learn about it. That is one of the reasons why they are shocked or confused when they meet people from different cultures with different customs. I examine the topic through the opinions of well-known experts and through my own experiences. I give a lesson based on the topic of table manners and customs in England which are different from ours and I compile a questionnaire. The answers of my students make it clear that my supposition is true.
Keywords: Pedagógusképzés